Paciente de sexo femenino de 27 años de edad en estado de gestación con hipertensión arterial. - Baños Sánchez, Grace Mishell (2021)
The clinical case to be treated is a 27-year-old patient with 24 weeks of gestation who presents with arterial hypertension with symptoms of migraine headache and a family pathological history of arterial hypertension. The objective of the present study is to maintain blood pressure control in pregnancy through the process of nutritional care and medical treatment. The estimated preconception weight formula was carried out, and a value of 69.9 kg was obtained, with which it was carried out through the weight gain formula giving us a result of 6.1 that through the curves were was able to observe that they present inadequate weight gain due to excess in their nutrition, For this reason, a respective nutritional plan was preceded by distributing 380 calories at breakfast, 439 calories in the morning, 655 calories in lunch, 173 calories in the afternoon and 453 calories in the snack, resulting in 2,100 kcal, covering the caloric needs during the day, divided into 5 meal times, by means of the Mifflin St Jeor equation. Blood pressure was controlled, at the beginning it was 139/89 mm Hg, through nutritional intervention it was possible to maintain the hypertensive state at 124/76 mm Hg, in addition to medical treatment with antihypertensive drugs such as methyldopa and acetyl salicylic acid. To conclude, through follow-up, it was possible to verify its improvement with nutritional treatment and it was indeed observed that there is a greater adherence to healthy eating, therefore it is necessary to establish an eating pattern to be able to control certain complications that may lead to future problems.